A treatment strategy for proximal femoral benign bone lesions in children and recommended surgical procedures: retrospective analysis of 62 patients - EROL, BÜLENT; TOPKAR, OSMAN MERT (SPRINGER, 2016)
We aimed to develop a surgical treatment strategy for benign bone lesions of the proximal femur based upon retrospective review of our data in 62 children. Sixty-two children [38 male, 24 female; median age 9 years (range 5-18 years)] with proximal femoral benign bone lesions were surgically treated between 2005 and 2013. Histopathological diagnoses were simple (31) or aneurysmal (27) bone cysts, and nonossifying fibromas (4). The pathological fracture rate was 77.4 %. Surgical treatment was determined due to four criteria, including patient's skeletal maturity, localization and initial diagnosis of lesion, and amount of bone loss in the femoral neck and lateral proximal femur. Surgical procedure consisted of biopsy, curettage, bone grafting, and internal fixation when required. The median follow-up was 45 months (range 25-89 months). Complete clinical recovery was achieved in 56 (90.3 %) patients between 4 and 8 months postoperatively; full weight-bearing and mobilization, without pain and limping, was possible. The median preoperative and postoperative last follow-up Musculoskeletal Tumor Society (MSTS) scores were 13.3 % (range 10-23.3 %) and 96.6 % (range 90-100 %), respectively (p < 0.0001). The pathological fractures were healed in 10 weeks on average (range 8-12 weeks). Fifty-seven (92 %) patients demonstrated complete or significant partial radiographic healing between 5 and 7 months that maintained throughout follow-up. Local recurrence was not observed, and only 1 (1.6 %) patient required reoperation for partial cyst healing. There were 5 (8 %) complications, 1 (1.6 %) of which required reoperation. This treatment strategy can provide good local control and excellent functional and radiological results in the management of benign bone lesions of the proximal femur in children.
Keywords: Benign bone tumor; Bone cyst; Proximal femur; Pathological fracture; Children; PATHOLOGICAL FRACTURES; LONG BONES; CYSTS; CURETTAGE; TUMORS; EXPERIENCE; RECURRENCE; FEMUR; NECK